Antibacterial Assay of Green Tea (Camellia Sinensis L) Against the Growth of Enterococcus faecalis - Asmah, Nur; Mattulada, Indrya Kirana; Dodo, Arnetta Zahra Atifah (Journal of Syiah Kuala Dentistry Society, 2023)
Background: Enterococcus faecalis (E. faecalis) is often reported as an infectious agent in tooth root canals. Green tea leaves (Camellia sinesis L) contain active substances, namely catechins, which can act as an antibacterial. Research. Objective: To determine the antibacterial effectiveness of green tea extract (Camellia sinensis l) against the growth of Enterococcus faecalis bacteria. Methods: Researchers carry out tests in the laboratory, which are called laboratory experimental tests. The form of this research is Post-test Only Control Design. Researchers took samples using a purposive sampling technique with four treatments and six repetitions. The statistical test used is the Kruskal-Wallis test. Results: Based on the results of Kruskal Wallis, the p-value shows a value of 0.011 or a p-value of less than 0.05, which indicates that there is a significant difference between the Camellia sinensis L 25%, 50%, 75% treatment, and the positive control. Conclusion: Green tea extract (Camellia sinensis l) with concentrations of 25%, 50%, and 75% can inhibit E. faecalis' growth.